Studi Komparasi Pada Interior Klenteng Tien Kok Sie Di Surakarta Dan Klenteng Fuk Ling Miao Di Yogyakarta Ditinjau Dari Aspek Fengshui Dan Budaya Jawa - Santosa, Stephanie Clorinda (Intra, 2015)
Temple is a place of worship for the people of Tri dharma and as appreciation form the ancestral culture of Chinese community has a unique and high architectural art. The object of research selected Tien Sie Kok temple in Surakarta and Fuk Ling Miau temple in Yogyakarta. Both are temple stands at the cultural center and a place of worship of the Chinese community are standing with the support of the palace. The study was conducted with the aim to reveal comparative study of interior Tien Sie Kok temple in Surakarta and Fuk Ling Miau temple in Yogyakarta terms of aspects of feng shui and Javanese culture. Research using the comparative method of qualitative research. The data collected by literature study, direct observation, and interviews. Analysis found that acculturation of values feng shui with Javanese culture in Tien Sie Kok temple and Fuk Ling Miau temple of the sacred space location, number and shapes meaning of doors, decorative, construction and installation of ceiling forms. However acculturation dominant in Fuk Ling Miau temple of similarity location, direction toward, and the elevation of the floor. This proves Fuk Ling Miau temple in Yogyakarta more follow the values of javanese culture.